Finite element modeling of soft ground improved by PVD using vacuum and surcharge preloading - Tarefder, Md. Rafiqul Alam; Lin, Der Guey; Bergado, Dennes T.; Noppadol Phien-Wej; The Government of Japan (Bangkok : Asian Institute of Technology, 1998)
This study presents the numerical computation of consolidation of soft Bangkok clay improved by Prefabricated Vertical Drain (PVD) using vacuum and surcharge preloading for the proposed Second Bangkok International Airport (SBIA) at Nong Ngu Hao site. The finite element code SAGE CRISP, is employed to investigate the improved soft ground. To simulate the effect of three dimensional (3-D) characteristics, a two dimensional (2-D) plane strain model is developed and an equivalent permeability concept with an adjusted width of drainage are applied to the PVD improved ground. Two dimensional pe1meability is obtained by considering equal discharge rate in both the 2-D model and the in situ case. Previous studies for soft Bangkok clay, such as the ratio of horizontal soil pe1meability (k1 .) to smeared zone permeability (k8 ), (ki/ =10) and the ratio of smeared zone diameter (d8) to equivalent drain diameter (dw), (d/ dw=2.5) is also used in permeability conversion. In 2-D plane strain model, the drains are considered as the drain boundaries. Vacuum is simulated by specifying negative pore pressure on the nodes of these boundaries and sand blanket. Excellent agreement between the observed and predicted settlement, and pore pressure were obtained. Therefore, the modeling procedures can be well established for the PVD improved ground with vacuum type of preloading. The similar embankment was also analyzed without vacuum. It was found that maximum vertical settlement at the centerline of the embankment decreased by 0.57 times comparing to vacuum preloading, whether maximum lateral displacement at the toe of embankment increased by 1.56 times. A further analysis was carried out to calculate the equivalent surcharge fill that will cause the rate of settlement equivalent to the case of vacuum preloading. The equivalent surcharge fill of 4m was found and which will cause a lateral deformation 2.75 times of the case of vacuum preloading. The back calculated undrained shear strength values of improved soil, S11 are increased more than 1. 7 times of the initial undrained shear strength, S110 for vacuum preloading. A normalized defo1mation behavior is also discussed.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology
Keywords: Vertical drains; Finite element method; Second Bangkok International Airport